The Role of Women’s Leadership in Enhancing Work-Life Balance and Flexible Work Arrangements: A Study in the Financial Industry - Bebasari, Nataliana; Parulian, Parulian; Daspar, Daspar (Ilomata International Journal of Social Science, 2025)
This study analyzes the influence of women's leadership on implementing flexible work arrangements (FWA), with work-life balance (WLB) acting as a mediator, in the financial industry in West Java and Jakarta. Using a quantitative approach, data were collected from 110 respondents working in various financial institutions and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that women’s leadership significantly and positively affects the adoption of FWA, primarily through its impact on employees' WLB. Women leaders are shown to have a deeper understanding of the importance of balancing work and personal life, which fosters the successful implementation of flexible work practices. This research contributes to the existing literature on women's leadership, work-life balance, and flexible work policies, particularly in the financial sector. From a practical standpoint, the results provide important insights for organizations aiming to develop leadership strategies and inclusive work policies that promote employee well-being and organizational effectiveness through better WLB and FWA practices.